A novel frameshift mutation in the fibrinogen γC terminal region, FGG c.1169_1170 del AT, leading to hypofibrinogenemia. Issue 159 (November 2017) - Nagata, Kazuhiro; Arai, Shinpei; Taira, Chiaki; Sugano, Mitsutoshi; Honda, Takayuki; Okumura, Nobuo
Highlights: We encountered a novel hypofibrinogenemia patient. The patient had a heterozygous nucleotide deletion with FGG c.1169_1170 del AT. This resulted in a frameshift (FS) mutation between codons 364 and 422 in the γ-chain. This also resulted in a FS mutation between codons 364 and 418 in the γ'-chain. These FS mutations did not synthesize the variant fibrinogen in CHO cell lines.